Drinking water biofilm monitoring by Propella™ and flow cell bioreactors under different operating conditions - Simões, Lúcia C. (2008)
Monitoring of biofilm subjected to different process conditions was performed using two distinct bioreactors, Propella™ and flow cell system. Biofilms were grown on polyvinyl chloride (PVC) and stainless steel (SS) coupons under laminar (Reynolds number of 2000) and turbulent (Reynolds number of 11000) flow. The parameters analyzed were culturable cells, using R2A, and total bacteria, which were assessed using a DNA-binding stain coupled with epifluorescence microscopy. The impact of the different operating conditions in the studied parameters was established after the biofilms reached the steady-state. It was found that the biofilm steady-state was achieved 3 d after the starting of operating conditions for turbulent flow and for both bioreactors and adhesion surfaces. Under laminar flow it was only achieved 6 d after. The number of total bacteria was invariably higher than the culturable cells. The number of total and culturable bacteria in turbulent flow-generated biofilms were similar in both bioreactors, regardless the adhesion surface tested. Under laminar flow, the Propella™ bioreactor allowed the formation of steady-state biofilms with a higher number of total and culturable bacteria than those from the flow cell system. Comparing the effect of the flow regime on biofilm accumulation, only turbulent flow-generated biofilms formed on the flow cell system had a higher amount of total and culturable bacteria than those formed under laminar flow. In terms of adhesion surface effect on steady-state biofilms, a higher number of total and culturable cells were found on PVC surfaces comparatively to SS when biofilms were formed using the flow cell system. Biofilm formation on PVC and SS was similar in the Propella™ system for both flow regimes.